Pelatihan dan Perbaikan Sistem Akuntansi di Pusat Rehabilitasi Sabatu - Okevanrianus Putra Hernat; Hengky Leon (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Every organization needs a credible accounting system to facilitate the process of recording and accounting related to the receipt and expenditure of money. Without a credible accounting system, it will have a systemic impact and affect the main activities of the organization. This community service was attended by participants from the finance and accounting staff at the Sabatu Rehabilitation Center. This activity aims to provide consultation in correcting the shortcomings of the existing accounting system. This activity received a positive response from the participants. This activity starts from the introduction and understanding of the accounting system that is currently running then continued with the exposure of the shortcomings and weaknesses of the accounting system that has currently been implemented. This activity ended with providing suggestions for improvements to the accounting system in the future. This activity was held at 08.30 – 12.00 WIB and continued through communication media for further assistance. It is important for a foundation to have reliable financial statements. Reliable financial statements will reflect the actual financial condition experienced by the foundation. In addition to being precise in carrying out good accounting records, foundations need to control their assets.